Highly Active Absorbent for SO₂ Removal Prepared from Coal Ash (Part 1) - Nakagawa, K.; Yamada, K.; Tsurue, T.; Takeda, S.; Ishizaki, K.; Quialao, T. A.; Balais, W. A.; Herrera, A. B.; Pugal, D. L.; Bion, H. H.; Magpantay, C. G.; Abarquez, F. I.; et al. (Philippine Engineering Journal; Vol 19 No 1 (1998), 2021)
Coal ash samples from Batangas Coal-Fired Thermal Power Plant and limestone from a cement plant in Bulacan were used as raw materials for the preparation of highly active SO₂ absorbent. The prepared SO₂ absorbents were characterized to determine the effects of mineralogical composition, morphological structure and the type of coal ash used, on SO₂ removal efficiency/ The desulfurization activity of the SO₂ absorbents were determined by varying the curing conditions and Ca O content. Among the coal ashes, fly ash exhibited the highest SO₂ removal efficiency and longest effective absorption period. The SO₂ removal efficiency is closely dependent on the basic conditions during the preparation process of the SO₂ absorbents. The SO₂ absorptions activity increased with the reaction temperature and reached a maximum at 120⁰C for fly ash and 130⁰C for both bottom ash and slag. Maximum SO₂ removal efficiency was also attained by fly ash at 10 hour curing period. Bottom ash and slag had high activity at 15-20 hours of curing time. Ca O content in the range of 20 ~30% will give a high SO₂ absorption activity.